1991
DOI: 10.1007/bf00371125
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic subunit of cyclic AMP-dependent protein kinase directly inhibits sodium channel activities in guinea-pig ventricular myocytes

Abstract: We investigated the effects of the purified catalytic subunit (C subunit) of the cAMP-dependent protein kinase (A-kinase) on the cardiac Na+ channel currents. Single Na+ channel currents in guinea-pig ventricular myocytes were recorded using the patch clamp technique of the inside-out configuration. Application of C subunit decreased the peak average current and slowed the current decay, effects which were caused by decrease in the open probability of Na+ channels and increase in the first latency, whereas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Early studies with mammalian ventricular myocytes demonstrated a reduction in cardiac I Na in response to PKA. 23,24,28,29 However, relatively positive holding potentials were used. In subsequent investigations in which cells were held at more negative voltages (that would minimize the effects of the negative shift in inactivation), Na ϩ currents were increased by kinase stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies with mammalian ventricular myocytes demonstrated a reduction in cardiac I Na in response to PKA. 23,24,28,29 However, relatively positive holding potentials were used. In subsequent investigations in which cells were held at more negative voltages (that would minimize the effects of the negative shift in inactivation), Na ϩ currents were increased by kinase stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…3B) did not significantly affect the degree of channel recovery at any concentration of MgATP. It has previously been reported from our laboratory that the catalytic subunit of PKA harvested from porcine cardiac muscle inhibits sodium channel activity in isolated guinea-pig ventricular myocytes (Sunami et al 1991 as a substitute for protein kinases in the phosphorylation of target proteins, but the transferred thiophosphate is not readily removed by protein phosphatases (Eckstein, 1985). As shown in Fig.…”
Section: Methods Preparationmentioning
confidence: 96%
“…29,30 Using heterologous expression of cardiac Na ϩ channels in Xenopus oocytes and mammalian cell line, activation of PKA has been reported to increase I Na derived from both the rat (rH1) and human (hH1) channels. [31][32][33] In contrast, other studies have shown an inhibition of cardiac I Na via PKA activation in guinea pig ventricular myocytes 16,34 and neonatal rat cardiac myocytes. 35 The effects of PKA activation may be speciesspecific.…”
Section: Effects Of Camp Modulation On I Namentioning
confidence: 99%
“…Consistent with our results in the present studies, PKA activation has been documented to inhibit the cardiac I Na in guinea pig ventricular myocytes. 16,34 In addition, the differences observed could result from data obtained in the native versus expression system. [31][32][33] Previous evidence has suggested that ␤-adrenergic receptor-activated modulation of cardiac I Na can occur via both a fast direct G-protein activation as well as by the slower indirect phosphorylation pathway.…”
Section: Effects Of Camp Modulation On I Namentioning
confidence: 99%